Recursive Local Summation of RX Detection for Hyperspectral Image Using Sliding Windows - Liaoying Zhao; Weijun Lin; Yulei Wang; Xiaorun Li (Remote Sensing, 2018)
Anomaly detection has received considerable interest for hyperspectral data exploitation due to its high spectral resolution. Fast processing and good detection performance are practically significant in real world problems. Aiming at these requirements, this paper develops a recursive local summation RX anomaly detection approach by virtue of sliding windows. This paper develops a recursive local summation RX anomaly detection approach by virtue of sliding windows. A causal sample covariance/correlation matrix is derived for local window background. As for the real-time sliding windows, the